The historic senate vote of 16 September 1991 looking back and looking forward twenty-five years after - Simbulan, Roland G. (Philippine studies : historical and ethnographic viewpoints, 2018)
"On 16 September 1991 the Philippine Senate voted against a proposed treaty to extend the presence of United States military bases in the Philippines for another ten years. As an insider in the Senate from 1987 to 1995, I reflect on the significance of this historic vote, which signified victory for the nationalist movement. How was it possible for a traditionally conservative and pro-US institution like the Philippine Senate to brave American displeasure by rejecting treaty extension? I address this question from the perspective of the broad antinuclear and anti-bases movement in the Philippines, from which a step-by-step strategy was implemented."